Poland as a Place for Study in the Experiences of International Students - Monika Popow (University of Lower Silesia, 2015)
The aim of this paper is to reconstruct and analyze the meanings of Poland as a place for study as given by international students. The paper presents results of my research project titled "Learning in a transnational environment". Within the project, phenomenographic interviews with international students studying in Poland in the 2014-2015 academic year, were conducted. The paper presents the meanings given most frequently, as well as their interpretation. The last part of the paper presents the concept of global transition places, which is related to the findings of the study.